PROSEDUR PENGELOLAAN ARSIP UNTUK KEAMANAN DOKUMEN DI RSIA PURI BUNDA MALANG - Retha Dwi Putri Veraniansyah; Erlangga Andi Sukma (Adbis: Jurnal Administrasi dan Bisnis, 2019)
In every organization, institution or agency in the implementation of the daily activities cannot be separated from an administrative activity. One of administration activity is archival activities. One of the purposes of the filing activities are archives that are stored remain safe and secure. Security activities of the archive also needs to be done to keep the archive remains in losed and damaged. The methods of data analysis to support the work of this research were used qualitative analysis method and used the method of data collection by observation and interview. The results of the research it had been known that the security of the archive was not in accordance with existing theory. Security archive influenced by how Hospital of Puri Bunda Malang conducting the management of the archive in order to avoid loss and damage to the archive. The problem occured because there is no control in borrowing and lending system of the archives, no certain place to put in, bad disaster resistance building, and also the lack of detail in the saving procedure. The Hospital of Puri Bunda Malang needed to pay attention to the security of the archives as well as the stored maintenance records.